Using statistics in economics - Thomas, R. Leighton (McGraw-Hill, 2005)
The primary aim of this book is to provide a text for economics students, which gives a good balance between statistics and econometrics. The intention is to prepare students for an introductory course in econometrics, while instilling a clear understanding of statistics. It is suitable for first or second year courses in Introductory Statistics or Introductory Statistics and Econometrics on economics degrees. The book is characterized by Leighton Thomas' clear style of explanation, gained through 35 years of teaching experience.